The Subtle Knife - Peter Rautenbach (The Journal of Intelligence, Conflict and Warfare, 2019)
This article looks to tie together the polar opposite of hybrid warfare and nuclear deterrence. The reason for this is that hybrid warfare and its effects on nuclear deterrence need to be explored as there appear to be substantial increases in hybrid warfare’s usage. This article found that hybrid warfare has an erosion-like effect on nuclear deterrence because it increases the likelihood that nuclear weapons will be used. This may be due to both the fact that hybrid warfare can ignore conventional redlines, and because the cyber aspect of hybrid warfare has unintended psychological effects on how deterrence functions. How does this relate to nuclear war?  In short, cyber warfare attacks key concepts which make nuclear deterrence a viable strategy including the concepts of stability, clarity, and rationality. Therefore, hybrid warfare increases the chance of nuclear use.